Computer-enhanced learning in neuroanatomy - Tan, C K; Voon, F C; Rajendran, K (Medical education, 1989)
The recent development of powerful microcomputers and the introduction of object-oriented programming languages has now made available to educationists software that can be easily used to design and develop computer-based learning material. We have developed courseware and tutorware in the field of neuroanatomy which are pedagogically structured and yet provide multiple paths of learning for the individual student. Neuroanatomy is a difficult subject to learn because of the structural intricacy and functional correlations that it entails. The courseware enables students to approach the subject at different levels of difficulty and progress at their own pace towards a comprehensive understanding of structure and function aided by text integrated with graphics, sound and animation. A significant advantage to authors of similar courseware is the option to update the contents easily when necessary in the future.